Perbaikan kualitas tanah berpasir untuk kebun kopi dengan penambahan tanah liat dan kompos di Desa Bambang, Kecamatan Wajak - Nisfi Fariatul Ifadah; Zaenal Kusuma; Soemarno (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: This study focuses on the effect of applying clay and compost on improving the quality of sandy soil in terms of the physical and chemical quality of the soil so that it can be a solution to problems in managing sandy soil so that the land can be productive and sustainable. Methods: This study used a factorial completely randomized design (RAL-F) with 3 treatment factors, namely: Depth (K1: 0-30 cm, K2: 30-60 cm), Dosage of compost (M1: 0 ton ha-1 as control, M2: 20 ton ha-1), Percentage of mineral soil (T1: 0% as control, T2: 25%, T3: 50%). Each treatment was repeated 4 times to obtain 48 pot units for the experiment. Data collection is carried out every 2 weeks for soil pH data. As for the other observation parameters taken in the last week of the incubation process, the data taken are chemical data in accordance with predetermined observation parameters which include soil physical properties such as bulk density, specific gravity, porosity, moisture content, pF value and basic chemical properties such as pH, organic matter, P-Available, N-Total. Results: Based on the results of laboratory analysis, it was shown that there was an increase in the average value of pH H2O and pH KCl every week, where initially the pH of H2O was 5.3 (1 MSI) to 5.9 (11 MSI) and the pH of KCl was from 5.1 (1 MSI) to 5.5 (11 MSI). This proves that the addition of organic matter and clay to the soil can increase the soil pH value. In addition to an increase in soil pH, there was also an increase in other chemical properties (BO, total-N and available-P) as well as soil physical properties (BI, BJ, Porosity and pF 2.5). Conclusion: the addition of clay soil and compost can improve the quality of sandy soil, especially the soil chemistry characteristics.